ROLE SCHOLARS SOCIETY FORM AND INTELLECTUAL MULTICULTURAL - ., Sulistiani (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan)
Attitudes and behaviors that emerge are often unsympathetic, even very contrary to the cultural values of noble ancestors. Attitudes such as solidarity, respect for others, gotong royong began to fade. The arrogance of the majority culture as a result of the dominance lead to a lack of understanding the culture and interact with other people. Apart from the interests of both individuals and groups, often a dispute that not infrequently lead to disunity, mutual hostility and even war is a result of a different mindset, interpretation pattern point of view of what they think is the way to go, the best way, the solution to achieve their destination. So that the underlying conditions that declares the special attention it is necessary in every teaching the importance of togetherness, mutual understanding, mengedepankan tolerance, and the principle that religion handed down to this earth to bring peace and tranquility.